Image and Discursive Landscape: Reflections on Iconic Land Art of the American West (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
The writer, a interdisciplinary visual artist focusing on landscape and land use, took a trip in the fall of 2016 through various iconic land art sites with Texas Tech University’s Land Arts of the American West program. Immersive engagement with sites such as Robert Smithson’s Spiral Jetty (1968) and Michael Heizer’s Double Negative (1969-70) offered the opportunity to reflect—critically and experientially—on the ways that the land artists’ speculations on natural history and humanity’s experience of landscape resonate both with the planned degradation of the sites, and our new, more fraught relationship to environmental change.
Keywords: landscape; 70s